Physical oceanography measurements in the tidal inlet between the islands Spiekeroog and Langeoog, Wadden Sea, North Sea, 2017-03 - Thomas Henry Badewien; Magdalena J Chojnowski; Lisa Götz; Jens-Martin Herold; Jakob Jeuk; Jens Meyerjürgens; Jonas Müller; Sarah-Sophie Weil (PANGAEA, 2017)
The data were measured in the German North Sea between the East-Frisian Islands Spiekeroog and Langeoog with RB Otzum (ICBM) on March 14 and 16 2017. Conductivity, temperature and pressure were measured by means of a Seabird CTD (type 19plusV2). On March 14 2017 data were collected for an entire tidal cycle, starting at low tide; whereas on March 16 2017 we measured only a half tidal cycle, starting at high tide. The profiles were taken in the middle of the tidal inlet between the two islands. During the CTD cast, where the CTD was veered with a speed of around 0.1 m/s, the boat was drifting with the current. The positions and times given in the data set mark the beginning of each CTD cast. Dates and times are given in UTC. The data were transformed by using the SBE Data Processing Software. Only the downcast profile was used and a bin average (binsize = 0.1 m) was calculated with the software.